2020
DOI: 10.3390/ijms21165730
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Chloride Sensitivity in Yeast and Regulation of Translation

Abstract: For decades, lithium chloride (LiCl) has been used as a treatment option for those living with bipolar disorder (BD). As a result, many studies have been conducted to examine its mode of action, toxicity, and downstream cellular responses. We know that LiCl is able to affect cell signaling and signaling transduction pathways through protein kinase C and glycogen synthase kinase-3, which are considered to be important in regulating gene expression at the translational level. However, additional downstream effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(58 citation statements)
references
References 80 publications
4
54
0
Order By: Relevance
“…Overexpression of eIF4A is shown to recover sensitivity of the yeast cells to LiCl in galactose media. Similar observation has also been reported for other genes linked to the translation of structured mRNAs in yeast [15,16]. Deletion mutants for these genes showed increased sensitivity to LiCl.…”
Section: Introductionsupporting
confidence: 85%
See 3 more Smart Citations
“…Overexpression of eIF4A is shown to recover sensitivity of the yeast cells to LiCl in galactose media. Similar observation has also been reported for other genes linked to the translation of structured mRNAs in yeast [15,16]. Deletion mutants for these genes showed increased sensitivity to LiCl.…”
Section: Introductionsupporting
confidence: 85%
“…In the literature the molecular activities for PEX11 and RIM20 have not been linked to LiCl sensitivity making these genes intriguing target for further study. LiCl toxicity in yeast is thought to be caused by the accumulation of galactose intermediate metabolites, particularly galactose-1p [14,15]. It has been shown that LiCl inhibits the conversion of glucose-1-phosphate to glucose-6-phosphate via modifying the expression of the phosphoglucomutase enzyme PGM2 [11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…eIF4A has been implicated in yeast’s response to LiCl stress [ 8 ]. Overexpression of eIF4A has been found to restore yeast cell sensitivity to LiCl in a galactose medium [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%